Can Pain-Related Fear Be Reduced? The Application of Cognitive-Behavioural Exposure in Vivo - Johan WS Vlaeyen; Jeroen R de Jong; Patrick Onghena; Maria Kerckhoffs-Hanssen; Ank MJ Kole-Snijders (Pain Research and Management)
Although cognitive-behavioural treatments of patients with chronic pain generally are reported to be effective, customization might increase their effectiveness. One possible way to customize treatment is to focus the intervention on the supposed mechanism underlying the transition from acute to chronic pain disability. Evidence is accumulating in support of the conjecture that pain-related fear and associated avoidance behaviours are crucial in the development and maintenance of chronic pain disability. It seems timely to apply this knowledge to the cognitive-behavioural management of chronic pain. Two studies are presented here. Study 1 concerns a secondary analysis of data gathered in a clinical trial that was aimed at the examination of the supplementary value of coping skills training when added to an operant-behavioural treatment in patients with chronic back pain. The results show that, compared with a waiting list control, an operant-behavioural treatment with or without pain-coping skills training produced very modest and clinically negligible decreases in pain-related fear. Study 2 presents the effects of more systematic exposure in vivo treatment with behavioural experiments in two single patients reporting substantial pain-related fear. Randomization tests for AB designs revealed dramatic changes in pain-related fear and pain catastrophizing. In both cases, pain intensity also decreased significantly, but at a slower pace. Differences before and after treatment revealed clinically significant improvements in pain vigilance and pain disability.